Mitigating the Adverse Financial Effects of Natural Hazards on the Economies of South Eastern Europe : A Study of Disaster Risk Financing Options - Gurenko, Eugene N. (World Bank, Washington, DC, 2017)
Over the last few decades, the frequency of major disasters caused by the impact of natural hazards has increased significantly, causing an increase in losses, both total economic and insured. This considerable increase can be fully attributed to weather-related events, which are inherently linked to climate change. The European Union (EU) community, and particularly the countries of South Eastern Europe (SEE), is prone to natural hazards such as earthquakes, floods and forest fires. In the SEE countries, the adverse effects of natural calamities, most of which can be assigned to climate change, are already being felt in many sectors of economy and at the macro level. The main objectives of this study have been two-fold. On the one hand, the study has attempted to establish the extent of financial vulnerability of governments and households to natural hazards in ten countries of South Eastern Europe. On the other hand, the study aims to outline a range of practical solutions and policy recommendations for the problem of the growing financial exposure from disasters caused by the impact of natural hazards for governments, businesses and individuals.This study is intended for four principal audiences: government officials in SEE countries; World Bank staff involved in disaster risk financing and reconstruction projects; the international development community; and the private insurance and reinsurance industry. The structure of the report is as follows: Chapter I is an Introduction. Chapter II reviews the EU regional financial safety net mechanisms that can be mobilized in case of major disasters caused by the impact of natural hazards, focusing mainly on the EU Solidarity Fund. Chapter III examines the fiscal capacity of SEE countries to cope on their own with large disaster events. Chapter IV reviews the existing diverse experience in covering the losses from disasters caused by the impact of natural hazards in disaster risk insurance in France, Spain and Germany. Chapter V presents an overview of the state of disaster insurance markets in SEE countries. Chapter VI presents the main findings and policy recommendations.